2013
DOI: 10.1016/j.mechmat.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A viscoplastic model for rate-dependent hardening for asphalt concrete in compression

Abstract: This dissertation presents a new type of uniaxial viscoplastic rate model based on viscoelastic convolution integrals for explaining the behavior of asphalt concrete in compression under repeated loading. Triaxial compression cyclic tests carried out for long rest periods, with different loading times and two different pulse shapes, square and haversine by researchers at North Carolina State University were used in developing the model. These tests demonstrate that the evolution of permanent deformation depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 7 publications
0
15
0
7
Order By: Relevance
“…Essa metodologia ja foi validada nacionalmente , mas requer ainda a continuidade da pesquisa com vistas a realizar o maior nu mero possí vel de ensaios em misturas locais. Ale m de considerar o confinamento, o ensaio TSS possibilita o uso do Shift Model, derivado do modelo incremental viscopla stico (Choi et al, 2012;Subramanian et al, 2013), que analisa o comportamento de misturas asfa lticas quanto a resiste ncia a deformaça o permanente. A associaça o do Shift Model ao programa LVECD (Layered Viscoelastic Continuum Damage) (Eslaminia et al, 2012;Choi e Kim, 2014) permite a previsa o de desempenho de pavimentos asfa lticos quanto a essa falha.…”
Section: Deformação Permanente Em Misturas Asfálticasunclassified
“…Essa metodologia ja foi validada nacionalmente , mas requer ainda a continuidade da pesquisa com vistas a realizar o maior nu mero possí vel de ensaios em misturas locais. Ale m de considerar o confinamento, o ensaio TSS possibilita o uso do Shift Model, derivado do modelo incremental viscopla stico (Choi et al, 2012;Subramanian et al, 2013), que analisa o comportamento de misturas asfa lticas quanto a resiste ncia a deformaça o permanente. A associaça o do Shift Model ao programa LVECD (Layered Viscoelastic Continuum Damage) (Eslaminia et al, 2012;Choi e Kim, 2014) permite a previsa o de desempenho de pavimentos asfa lticos quanto a essa falha.…”
Section: Deformação Permanente Em Misturas Asfálticasunclassified
“…As the vehicular loads pass by the surface of the asphalt pavement, basically it is the process of repeated loading and unloading which can be described as cyclic rectangular, triangular, trapezoidal and haversine waves for a certain point in the above area [7,8]. Barksdale [9] investigated load pulses in different locations of flexible pavement and the results showed that the haversine load would appear to be a reasonable representation.…”
Section: Generalized Kelvin Model and The Determination Of Model Paramentioning
confidence: 99%
“…They investigated how to implement an incremental model for the rutting predictions developed by Yun (5) and Subramanian et al (6). The incremental model equation is …”
Section: Vp Modelmentioning
confidence: 99%